มโนทัศน์เรื่องความแปรเปลี่ยนในปรัชญาของจวงจื่อ - นารท ศรียามินธน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The Chuang-Tzu s concept of transformation could be considered into two aspects, namely transformation of nature and transformation of human epistemology. The Tao Te Ching considers the transformation of nature from a macrocosmic aspect, as abstract process of nature and regards the process of transformation as generation, unity, balance and harmony among all beings. The Chuang-Tzu considers the transformation of nature from a microcosmic aspect via particular beings such as human beings, animals and plants. The Chuang-Tzu extends the concept of transformation of nature by pointing out that in the transformation of nature; all beings exist in the stream of continuous transformation. With regard to the Chuang-Tzu{174}s open-ended nature, the transformation of nature indicates that death in nature is not an "end" to life but a stage wherein life pass on to another form. The Chuang-Tzu reveals that in the awareness of infinite transformation, human beings can relieve themselves from sufferings to achieve an enlighted state where their inner-self will be forgotten. In addition, the Chuang-Tzu also emphasizes the transformation of human epistemology resulting from inner cultivation. This transformation could drive the inner-self of human being into a nobler state. This transformation reveals the human condition as possessing a combination of aesthetic, virtuous and spiritual potentiality. In this aspect, human beings can co-operate with nature to determine the appropriate transformation for all beings. However this must be done with prudence and a profound understanding of nature.